Biomarkers and degree of atherosclerosis are independently associated with incident atherosclerotic cardiovascular disease in a primary prevention cohort: The ARIC study. (October 2016) - Agarwala, Anandita; Virani, Salim; Couper, David; Chambless, Lloyd; Boerwinkle, Eric; Astor, Brad C.; Hoogeveen, Ron C.; Coresh, Joe; Sharrett, A. Richey; Folsom, Aaron R.; Mosley, Tom; Ballantyne, Christie M.; et al.
Abstract: Background and aims: Biomarkers and atherosclerosis imaging have been studied individually for association with incident cardiovascular disease (CVD); however, limited data exist on whether the biomarkers are associated with events with a similar magnitude in the presence of atherosclerosis. In this study, we assessed whether the presence of atherosclerosis as measured by carotid intima media thickness (cIMT) affects the association between biomarkers known to be associated with coronary heart disease (CHD) and incident cardiovascular disease (CVD) in a primary prevention cohort. Methods: 8127 participants from the ARIC study (4th visit, 1996–1998) were stratified as having minimal, mild, or substantial atherosclerosis by cIMT. Levels of C-reactive protein, lipoprotein-associated phospholipase A2, cardiac troponin T, N-terminal pro-brain natriuretic peptide, lipoprotein(a), cystatin C, and urine albumin to creatinine ratio were measured in each participant. Hazard ratios were used to determine the relationship between the biomarkers and incident CHD, stroke, and CVD in each category of atherosclerosis. Results: While each of the biomarkers was significantly associated with risk of events overall, we found no significant differences noted in the strength of association of biomarkers with CHD, stroke, and CVD when analyzed by degree of atherosclerosis. Conclusions: These findings suggest that the level of atherosclerosis does not significantly influence the association between biomarkers and CVD. Highlights: Ultrasound measurements (cIMT/plaque) have been shown to be associated with incident CVD as have serum biomarkers. We tested whether atherosclerosis burden measured by cIMT/plaque affects the association of biomarkers with CVD. Associations between biomarkers and CVD were not affected by degree of atherosclerosis in this analysis from the ARIC study.